Evaluation of Preceptorship Implementation among Pharmacy Professional Program Students at Universitas Mataram across Practice Settings - Raisya Hasina; Siti Rahmatul Aini; Mahacita Andanalusia; Tuhfatul Ulya; Baiq Risky Wahyu Lisnasari; Winiayu Devhi Prasasthi; Baiq Aulia Ali; Gusti Ayu Pratitha Devinta Putri; Fawwaz Aqila Putri; Jasmine Zaskia Kaori (Universitas Pendidikan Mandalika, 2026)
Preceptorship is widely implemented in pharmacist professional education to facilitate experiential learning and competency development during the Pharmacist Professional Practice Program (PKPA). However, evaluations of its implementation across different practice settings remain limited. This study aimed to evaluate the implementation of the preceptorship method among students of the Pharmacist Professional Study Program (PSPPA), Faculty of Medicine and Health Sciences, Universitas Mataram, during PKPA in community pharmacies, hospitals, public health centers, and pharmaceutical wholesalers. This study employed a mixed-methods design using a sequential explanatory approach. Quantitative data were collected through a structured questionnaire administered to PSPPA students to assess perceptions of preceptorship implementation across six domains. Qualitative data were obtained through in-depth interviews with 11 preceptors and analyzed using thematic analysis to further explain the quantitative findings. The quantitative results showed that all assessment domains were categorized as “very good,” with scores ranging from 82.5% to 88.3%. The highest score was observed in the student skill development domain (88.3%), followed by preceptor involvement (86.6%) and knowledge assessment through evaluation and feedback (85.0%). Qualitative findings revealed that preceptorship was implemented through three main stages: orientation, implementation, and evaluation. Orientation facilitated students’ adaptation to practice environments, while the implementation stage involved direct supervision, reflective discussions, assignments, and progressive responsibility. Evaluation was conducted continuously through observation, feedback, portfolios, and collaborative monitoring between preceptors and academic supervisors. Challenges identified included limited preceptor availability, variations in student readiness, and the relatively short duration of PKPA placements. In conclusion, the preceptorship method was implemented effectively across PKPA settings and contributed positively to students’ competency development. Strengthening student preparation, institutional support, and collaboration between academic institutions and practice sites may further optimize preceptorship implementation.